2011
DOI: 10.1186/1471-2350-12-137
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic analysis of the effects of polymorphisms in APOE, IDE and IL1B on a ketone body based therapeutic on cognition in mild to moderate Alzheimer's disease; a randomized, double-blind, placebo-controlled study

Abstract: BackgroundTo examine the effect of genetic variation in APOE, IDE and IL1B on the response to induced ketosis in the Alzheimer's Disease Assessment Scale-Cognitive subscale (ADAS-Cog) in subjects with mild to moderate Alzheimer's disease (AD).MethodsGenotype effects on ADAS-Cog scores from a randomized, double-blind, placebo-controlled study in mild to moderate AD were examined by an overall two way analysis of variance. In addition, interactions with the carriage status of the epsilon 4 allele of the APOE gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 36 publications
1
30
1
Order By: Relevance
“…The authors suggested that the known allelic presentation of the IL-1b gene is not a direct regulator of the IL-1b production, and conversely, the IL-1RA allele 2 is associated to an elevated IL-1b production in vitro (Santtila et al 1998). However, other authors described enhanced IL-1b circulating levels in vivo in patients with T allele at -511 position (El-Omar et al 2000;Hall et al 2004;Henderson and Poirier 2011). The protective effect of CC genotype of IL-1b-544 SNP in neurodegeneration has been already proposed by some authors (Licastro et al 2000;Green et al 2002;Di Bona et al 2008;Déniz-Naranjo et al 2008;Henderson and Poirier 2011).…”
Section: Discussionmentioning
confidence: 90%
“…The authors suggested that the known allelic presentation of the IL-1b gene is not a direct regulator of the IL-1b production, and conversely, the IL-1RA allele 2 is associated to an elevated IL-1b production in vitro (Santtila et al 1998). However, other authors described enhanced IL-1b circulating levels in vivo in patients with T allele at -511 position (El-Omar et al 2000;Hall et al 2004;Henderson and Poirier 2011). The protective effect of CC genotype of IL-1b-544 SNP in neurodegeneration has been already proposed by some authors (Licastro et al 2000;Green et al 2002;Di Bona et al 2008;Déniz-Naranjo et al 2008;Henderson and Poirier 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Clinical trials have shown an improvement in ADAS-COG score in AD patients after 90 days (Henderson & Poirier 2011), however this difference was only present in non-ε4 carriers.…”
Section: Nutrimedicinementioning
confidence: 82%
“…For example, a trial of a medication which induced mild peripheral ketosis improved cognitive scores but only in E4 non-carrier participants. 105 These findings were not readily explained by differences in peripheral ketone body levels, and the authors speculated that the findings could be related to differences in brain transport of ketone bodies or their utilization.…”
Section: Triglycerides Cognition and Apoe Statusmentioning
confidence: 88%